MicroRNA-301a inhibition enhances the immunomodulatory functions of adipose-derived mesenchymal stem cells by induction of macrophage M2 polarization - Hsu, Li-Wen (Int J Immunopathol Pharmacol, 2020)
MicroRNAs (miRNAs) are a class of short non-coding RNAs that play a significant role in biological processes in various cell types, including mesenchymal stem cells (MSCs). However, how miRNAs regulate the immunomodulatory functions of adipose-derived MSCs (AD-MSCs) remains unknown. Here, we showed that modulation of miR-301a in AD-MSCs altered macrophage polarization. Bone marrow (BM)-derived macrophages were stimulated with LPS (1 μg/ml) and co-cultured with miRNA transfected AD-MSCs for 24 h. The expression of M1 and M2 markers in macrophages was analyzed. Inhibition of miR-301a induced M2 macrophage with arginase-1, CD163, CD206, and IL-10 upregulation. Additionally, toll-like receptor (TLR)-4 mRNA expression in macrophages was downregulated in co-cultures with AD-MSCs transfected with a miR-301a inhibitor. Nitric oxide (NO) in the supernatant of AD-MSC/macrophage co-culture was also suppressed by inhibition of miR-301a in AD-MSCs. We further found that suppression of miR-301a in AD-MSCs increased prostaglandin E(2) (PGE2) concentration in the conditioned medium of the co-culture. Taken together, the results of our study indicate that miR-301a can modulate the immunoregulatory functions of AD-MSCs that favor the applicability as a potential immunotherapeutic agent.